A pervaporatively gasifying membrane and its method of manufacture and use
Patent Information
- Application Number
- CN202611069278.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]目前,增强Pebax膜材料分离性能的方法有多种,如增加分离层厚度、热处理或与甲苯二异氰酸酯交联等,这些方法虽然可以提高膜分离的选择性,但往往以降低渗透通量来换取选择性的提高
(1)本发明通过先成膜后改性,简单、有效地实现渗透气化膜材料的制备。在强极性溶剂DMF中,Pebax的长链舒展,芳基二缩水甘油醚的小分子均匀分散在Pebax的聚醚软段区域。由Pebax端羟基亲核进攻环氧基团发生开环加成,并伴随部分环氧自聚。反应新生成的羟基可与Pebax硬段酰胺结构(-CONH-)中的N-H和羰基C=O形成致密氢键网络。依托Pebax本征的软硬段相分离结构,该氢键作用将芳基二缩水甘油醚有效锚定在聚醚软段区域并形成局部固化微区;再叠加芳基二缩水甘油醚中苯环与芳烃分子间的π-π相互作用,最终实现了芳烃传输效率的提升,使得渗透气化膜在保证膜分离选择性的同时,可提高膜渗透通量,渗透通量可提高25-60%,综合分离性能评价指标(PSI)可达到11-13,具有优异的综合分离性能,是目前已知分离甲苯/正庚烷膜材料最高的PSI。
Smart Images

Figure CN122912708A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane separation technology, and specifically relates to a pervaporation membrane, its preparation method, and its application. Background Technology
[0002] The separation of alkane / aromatic mixtures is of great significance in the petrochemical industry. However, due to the similar physicochemical properties of alkanes and aromatics and their tendency to form near-boiling or azeotropic compounds, their separation is very difficult. Membrane separation technology, with its advantages of low energy consumption, high selectivity, and environmental friendliness, shows potential application value in the field of liquid-phase molecular separation.
[0003] Pebax, a polyether-polyamide block copolymer, combines high strength with excellent solvent resistance thanks to the synergistic effect of rigid polyamide segments and flexible polyether segments. This material exhibits good film-forming properties, and due to its solubility parameters being similar to those of aromatics, it has a natural affinity for aromatic media, making it suitable for aromatic separation and transport applications.
[0004] Currently, there are various methods to enhance the separation performance of Pebax membrane materials, such as increasing the thickness of the separation layer, heat treatment, or crosslinking with toluene diisocyanate. Although these methods can improve the selectivity of membrane separation, they often come at the cost of reducing the permeate flux.
[0005] Therefore, it is of great significance to provide a pervaporation membrane that can improve membrane permeation flux while ensuring membrane separation selectivity. Summary of the Invention
[0006] The present invention aims to solve one or more technical problems existing in the prior art, and at least provide a beneficial solution. Specifically, the present invention provides a pervaporation membrane that, while ensuring membrane separation selectivity, can improve membrane permeation flux and has excellent overall separation performance.
[0007] The inventive concept of this invention: The pervaporation membrane of this invention includes a base membrane and a separation layer stacked together, wherein the separation layer is composed of an aryl diglycidyl ether crosslinked modified polyether-polyamide block copolymer.
[0008] The separation layer of this invention comprises a polyether-polyamide block copolymer crosslinked and modified with aryl diglycidyl ether. During the crosslinking modification process, the terminal hydroxyl groups of the polyether-polyamide block copolymer nucleophilically attack the epoxy groups, undergoing ring-opening addition, accompanied by partial epoxy self-polymerization. The newly generated hydroxyl groups can form a dense hydrogen bond network with the NH and carbonyl C=O groups in the Pebax hard segment amide structure (-CONH-). Relying on the intrinsic soft and hard segment phase separation structure of Pebax, this hydrogen bonding effectively anchors the aryl diglycidyl ether in the polyether soft segment region and forms locally solidified micro-regions. Simultaneously, the superimposed π-π interaction between the benzene ring in the aryl diglycidyl ether and the aromatic molecules ultimately improves the aromatic hydrocarbon transport efficiency. This allows the pervaporation membrane to increase the membrane permeate flux while maintaining membrane separation selectivity, with a permeate flux increase of 25-60%. The overall separation performance index (PSI) can reach 11-13, demonstrating excellent overall separation performance.
[0009] Therefore, a first aspect of the present invention provides a permeation vaporization membrane.
[0010] Specifically, the pervaporation membrane comprises a base membrane and a separation layer stacked together, wherein the separation layer comprises an aryl diglycidyl ether crosslinked modified polyether-polyamide block copolymer.
[0011] Specifically, the separation layer is located on one side surface of the base film.
[0012] Preferably, in the aryl diglycidyl ether crosslinked modified polyether-polyamide block copolymer, the aryl diglycidyl ether includes at least one of bisphenol A diglycidyl ether (BADGE), bisphenol S diglycidyl ether, and bisphenol F diglycidyl ether.
[0013] Preferably, in the aryl diglycidyl ether crosslinked modified polyether-polyamide block copolymer, the polyether-polyamide block copolymer is selected from at least one of Arkema 2533 (Pebax 2533), 3533 (Pebax 3533), and 4033 (Pebax 4033).
[0014] Preferably, the base membrane comprises a polytetrafluoroethylene (PTFE) filter membrane; more preferably, the PTFE filter membrane is a PTFE ultrafiltration membrane.
[0015] Preferably, the pore size of the polytetrafluoroethylene filter membrane is 0.1-0.45 μm; for example, any value within the range of 0.1-0.45 μm can be used, such as 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.45 μm, etc.
[0016] A second aspect of the present invention provides a method for preparing the permeation vaporization membrane described in the first aspect of the present invention.
[0017] Specifically, the preparation method of the pervaporation membrane includes the following steps: The polyether-polyamide block copolymer solution was coated onto the surface of the base film, and then crosslinked and modified in an aryl diglycidyl ether solution to obtain the final product.
[0018] Preferably, a polyether-polyamide block copolymer solution is coated on one side surface of the base film.
[0019] Preferably, the method for preparing the polyether-polyamide block copolymer solution includes the following steps: The polyether-polyamide block copolymer is prepared by mixing it with a solvent and heating it.
[0020] Preferably, the polyether-polyamide block copolymer is washed and dried before mixing.
[0021] Preferably, the solvent includes N,N-dimethylformamide (DMF).
[0022] Preferably, the mass fraction of the polyether-polyamide block copolymer solution is 8-12 wt%; for example, any value within the range of 8-12 wt% can be used, such as 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, etc.
[0023] Preferably, the heating temperature is 90-110℃ and the heating time is 2-3h; for example, the heating temperature can be any value within the range of 90-110℃, such as 90℃, 95℃, 100℃, 105℃, 110℃, etc.; the heating time can be any value within the range of 2-3h, such as 2h, 2.5h, 3h, etc.
[0024] Preferably, stirring is performed during the heating process, and the stirring speed is 400-600 rpm; for example, any value within the range of 400-600 rpm can be used, such as 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, etc.
[0025] Preferably, the heating method includes oil bath heating.
[0026] Preferably, the coating method includes spin coating, and the spin coating speed is 300-1100 rpm; for example, any value in the range of 300-1100 rpm can be used, such as 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, etc.
[0027] Preferably, the coating is followed by drying, and the drying process is to dry at 25-30℃ for 12-24 hours, and then at 40-140℃ for 3-12 hours.
[0028] Preferably, after coating and drying, Pebax / PTFE membrane material is obtained.
[0029] Preferably, the solvent in the aryl diglycidyl ether solution includes DMF.
[0030] Preferably, the mass fraction of the aryl diglycidyl ether solution is 2-10 wt%; for example, any value within the range of 2-10 wt% can be used, such as 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, etc.
[0031] Preferably, the crosslinking modification temperature is 35-45℃, and the crosslinking modification time is 12-24h; for example, the crosslinking modification temperature can be any value within the range of 35-45℃, such as 35℃, 40℃, 45℃, etc.; the crosslinking modification time can be any value within the range of 12-24h, such as 12h, 16h, 20h, 24h, etc.
[0032] Preferably, the crosslinking modification is followed by drying, the drying temperature is 100-120℃, and the drying time is 3-6 hours.
[0033] A third aspect of the present invention provides an application of the pervaporation membrane described in the first aspect of the present invention in the separation of alkane / aromatic mixtures.
[0034] Compared with the prior art, the beneficial effects of the technical solution provided by the present invention are as follows: (1) This invention achieves the simple and effective preparation of pervaporation membrane materials by first forming a film and then modifying it. In the highly polar solvent DMF, the long chain of Pebax extends, and the small molecules of aryl diglycidyl ether are uniformly dispersed in the polyether soft segment region of Pebax. Ring-opening addition occurs due to the nucleophilic attack of the terminal hydroxyl groups of Pebax on the epoxy groups, accompanied by partial epoxy self-polymerization. The newly generated hydroxyl groups can form a dense hydrogen bond network with the NH and carbonyl C=O in the hard segment amide structure (-CONH-) of Pebax. Based on Pebax's intrinsic soft-hard segment phase separation structure, the hydrogen bonding effectively anchors aryl diglycidyl ether in the polyether soft segment region and forms locally solidified micro-regions. This, combined with the π-π interactions between the benzene ring and aromatic molecules in the aryl diglycidyl ether, ultimately improves the aromatic hydrocarbon transport efficiency. This allows the pervaporation membrane to maintain membrane separation selectivity while increasing membrane permeate flux by 25-60%, achieving a Power Separation Index (PSI) of 11-13. This demonstrates excellent overall separation performance and represents the highest known PSI for toluene / n-heptane separation membrane materials.
[0035] (2) The present invention uses a membrane material of Pebax 4033 / PTFE crosslinked with bisphenol A diglycidyl ether. Under the conditions of 40°C and a feed of 50 / 50wt% toluene / n-heptane mixture, the permeation flux of the crosslinked modified pervaporation membrane is 36198.7 gm. -2 h -1 The separation factor was 1.37. The permeation flux of the uncrosslinked modified pervaporation membrane was 22624.2 gm³. -2 h -1 The separation factor is 1.34. Compared with the uncrosslinked membrane material, the permeation flux of the pervaporation membrane modified by bisphenol A diglycidyl ether crosslinking in this invention is increased by 60%, while the separation factor remains basically unchanged, that is, the performance of the modified membrane is significantly improved. Attached Figure Description
[0036] Figure 1 The infrared spectra of the Pebax4033 film and the 4B-Pebax4033 film of the present invention are shown below. Figure 2 Thermogravimetric curves of the Pebax4033 membrane and the 4B-Pebax4033 membrane of this invention are shown. Figure 3 The graph shows the comparison results of the separation performance of the pervaporation membranes in Examples 1-2 and Comparative Examples 1-3 of the present invention. Figure 4 The graph shows the comparison results of the pervaporation separation index of the permeation vaporization membranes in Examples 1-2 and Comparative Examples 4-5 of the present invention. Detailed Implementation
[0037] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.
[0038] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.
[0039] Example 1 This embodiment provides a pervaporation membrane, which consists of a base membrane polytetrafluoroethylene ultrafiltration membrane (pore size of 0.1 μm) and a separation layer stacked together. The separation layer is composed of BADGE crosslinked modified polyether-polyamide block copolymer (Arkema, France, Pebax 4033).
[0040] This embodiment also provides a method for preparing the above-mentioned pervaporation membrane, the steps of which are as follows: (1) Preparation of Pebax4033 casting solution: Pebax4033 was washed with deionized water and anhydrous ethanol in sequence and dried; dried Pebax4033 and DMF were loaded into a three-necked flask, wherein the mass fraction of Pebax4033 was 10wt%; the sealed three-necked flask was placed in an oil bath at 100℃ and magnetically stirred at 500rpm for 2h to form a uniform and stable casting solution; (2) While hot (in this embodiment, the casting solution temperature is 90°C), spin-coat the casting solution onto the surface (one side) of the polytetrafluoroethylene ultrafiltration membrane at a spin-coating speed of 500 rpm and a spin-coating time of 60 s; then dry the membrane material at room temperature (25°C) for 12 h, and then at 120°C for 3 h to obtain the original Pebax 4033 / PTFE membrane; (3) Dissolve BADGE in DMF at room temperature (25℃) with a mass fraction of 4wt%; place the dried Pebax 4033 / PTFE membrane from step (2) into a petri dish, then add 5g of DMF mixed solution containing 4wt% BADGE, and carry out the crosslinking reaction at 40℃ for 12h, and then dry at 100℃ for 3h to obtain the BADGE crosslinked modified Pebax4033 / PTFE membrane, namely 4B-Pebax4033 / PTFE membrane (referred to as membrane 1).
[0041] Example 2 This embodiment provides a pervaporation membrane, which consists of a base membrane of polytetrafluoroethylene ultrafiltration membrane (pore size of 0.1 μm) and a separation layer stacked together. The separation layer is composed of BADGE crosslinked modified polyether-polyamide block copolymer (Arkema, France, Pebax 2533).
[0042] This embodiment also provides a method for preparing the above-mentioned pervaporation membrane, the steps of which are as follows: (1) Preparation of Pebax2533 casting solution: Pebax was washed with deionized water and anhydrous ethanol and dried; dried Pebax2533 and DMF were loaded into a three-necked flask, with the mass fraction of Pebax2533 being 10wt%; the sealed three-necked flask was placed in an oil bath at 100℃ and magnetically stirred at 500rpm for 2h to form a uniform and stable casting solution; (2) While hot (in this embodiment, the casting solution temperature is 90°C), spin-coat the casting solution onto the surface (one side) of the polytetrafluoroethylene ultrafiltration membrane at a spin-coating speed of 300 rpm and a spin-coating time of 60 s; then dry the membrane material at room temperature (25°C) for 12 h, and then dry it at 100°C for 6 h to obtain the original Pebax2533 / PTFE membrane. (3) The only difference from step (3) of Example 1 is that the Pebax4033 / PTFE membrane is replaced with the Pebax2533 / PTFE membrane prepared in step (2), and the rest is the same as step (3) in Example 1, to obtain the BADGE crosslinked Pebax2533 membrane, namely 4B-Pebax2533 / PTFE (denoted as membrane 2).
[0043] Comparative Example 1: The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not perform step (3), while the rest is the same as Example 1, resulting in a Pebax4033 / PTFE membrane (denoted as membrane 3).
[0044] Comparative Example 2 The only difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not perform step (3), while the rest is the same as Example 2, resulting in a Pebax2533 / PTFE membrane (denoted as membrane 4).
[0045] Comparative Example 3: Steps (1) and (2) of Comparative Example 3 are the same as those of Example 1, resulting in a Pebax4033 / PTFE membrane. Step (3) of Comparative Example 3 is as follows: 4,4'-diphenylmethane diisocyanate (MDI) was dissolved in DMF at room temperature (25°C), with a mass fraction of 4 wt% MDI. The dried Pebax4033 / PTFE membrane was placed in a petri dish, and then 5 g of a DMF mixed solution containing 4 wt% MDI was added. The crosslinking reaction was carried out at 40°C for 12 h, and then dried at 100°C for 3 h to obtain the MDI crosslinked Pebax4033 / PTFE membrane, namely the 4M-Pebax4033 / PTFE membrane (denoted as membrane 5).
[0046] Comparative Example 4 Comparative Example 4 uses a method in the prior art (Science., 2024, 386, 1037-1042), namely, a stepwise spin coating method, to prepare a hybrid matrix membrane material with UiO-66 oriented monolayer continuously distributed, which is anchored and repaired by hyperbranched polymers, as a permeation vaporization membrane.
[0047] Comparative Example 5 Comparative Example 5 uses a method in the prior art (Journal of Membrane Science., 2026, 740, 124998), namely, TpPa-SO3Ag nanosheets are incorporated into Pebax to prepare a TpPa-SO3Ag / Pebax hybrid matrix membrane as a pervaporation membrane.
[0048] Performance testing 1. Infrared spectroscopy and thermogravimetric analysis To avoid the influence of the base membrane (PTFE filter membrane) on the characterization results, Pebax4033 membrane and 4B-Pebax4033 membrane were prepared for infrared spectroscopy and thermogravimetric analysis, respectively.
[0049] The preparation process of the 4B-Pebax4033 membrane is as follows: the casting solution is cast into a polytetrafluoroethylene petri dish instead of spin-coating it onto a polytetrafluoroethylene ultrafiltration membrane. The rest of the process is the same as in Example 1, and the 4B-Pebax4033 membrane is obtained.
[0050] The preparation process of the Pebax4033 membrane differs from that of the 4B-Pebax4033 membrane only in that BADGE was not added for crosslinking modification. Otherwise, the preparation process is the same as that of the 4B-Pebax4033 membrane, and it serves as a blank control group.
[0051] Infrared spectroscopy and thermogravimetric analysis were performed on Pebax 4033 membrane and 4B-Pebax 4033 membrane. The infrared spectra are shown below. Figure 1 As shown, the thermogravimetric curve is as follows Figure 2 As shown.
[0052] Depend on Figure 1 and Figure 2 It can be seen that 1509cm -1 This peak typically corresponds to the C=C stretching vibration of the aromatic ring, but it was not observed in the Pebax 4033 membrane of the blank control group. Furthermore, compared to the Pebax 4033 membrane, the 4B-Pebax 4033 membrane exhibited enhanced thermal stability, indicating that BADGE was successfully crosslinked onto Pebax 4033. 2. Pervaporation separation experiment The pervaporation membranes prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to pervaporation separation experiments to evaluate their separation performance. The pervaporation separation experiment process was as follows: The pervaporation membranes prepared in Examples 1-2 and Comparative Examples 1-3 were cut into Φ5cm circular pieces with the separation layer facing the feed liquid side and placed on the surface of the support porous plate of the pervaporation test cell. A polytetrafluoroethylene sealing gasket was laid on top of the membrane and locked up and down with clamps to compress and fix the membrane module. Then, the alkane / aromatic mixture to be separated was added upstream of the membrane, and a serpentine cold trap and a vacuum pump were connected downstream of the membrane in sequence to check the airtightness of the system. After the airtightness was good, the serpentine cold trap was placed in a liquid nitrogen cup, and a certain amount of liquid nitrogen or dry ice (liquid nitrogen was used in this test) was poured in as a cold source. After waiting for 5 minutes, when the cold hydrazine and liquid nitrogen were in full contact, the vacuum pump was turned on to carry out the pervaporation separation experiment. During the separation process, the raw material content, the product content collected in the liquid nitrogen cup, the separation time and other data were recorded to facilitate the evaluation of the membrane separation performance of the prepared pervaporation membrane.
[0053] The calculation methods for permeate flux (J), separation factor (β), and perevaporation separation index (PSI) in membrane pervaporation separation are as follows: Permeation flux (J) = W / (A×T); Separation factor (β) = (Y i / Y j ) / (X i / X j ); Pervaporation Separation Index (PSI) = J × (β-1); W: Mass of permeate, in g; A: Effective membrane separation area, unit: m² 2 ; T: Membrane separation time, in hours; Y i Y j : Mole fraction of permeate components i and j; X i X j : Mole fraction of feed liquid components i and j.
[0054] The pervaporation membranes of Examples 1-2 and Comparative Examples 1-3 were used for pervaporation separation of toluene / n-heptane mixtures. The separation performance of each group of pervaporation membranes was compared under the conditions of 40°C and a 50 / 50 wt% toluene / n-heptane mixture. Figure 3 As shown.
[0055] Depend on Figure 3 It can be seen that the permeation flux of the pervaporation membrane in Example 1 is 36198.7 gm. -2 h -1The separation factor was 1.37, and the pervaporation separation index was 13.39 kg m³. -2 h -1 Example 2: The permeation flux of the pervaporation membrane was 28680.1 gm³. - 2 h -1 The separation factor was 1.32, and the pervaporation separation index was 9.18 kg m³. -2 h -1 .
[0056] The permeation flux of the pervaporation membrane in Comparative Example 1 was 22624.2 gm. -2 h -1 The separation factor was 1.34, and the pervaporation separation index was 7.69 kg m³. -2 h -1 The permeation flux of the pervaporation membrane in Comparative Example 2 was 25436.9 gm. -2 h -1 The separation factor was 1.31, and the pervaporation separation index was 7.89 kg m³. -2 h -1 .
[0057] A comparison of Comparative Examples 1-2 with Examples 1-2 shows that introducing bisphenol A diglycidyl ether into Pebax membrane materials can improve the membrane's permeability to toluene while maintaining separation selectivity, and also exhibits an excellent permeate-evaporation separation index.
[0058] The permeation flux of the pervaporation membrane in Comparative Example 3 was 18710.8 gm. -2 h -1 The separation factor was 1.35, and the pervaporation separation index (PSI) was 6.55 kg m³. -2 h -1 As can be seen, compared with bisphenol A diglycidyl ether modification, the permeate flux of the membrane material modified by MDI did not increase but decreased. This indicates that the present invention uses a specific aryl diglycidyl ether as a crosslinking modifier, which can improve the permeate flux of the membrane while maintaining separation selectivity and obtain an excellent pervaporation separation index.
[0059] Using the same experimental and calculation methods as described above, the pervaporation membranes of Comparative Examples 4-5 were used for pervaporation separation of toluene / n-heptane mixtures. Under the conditions of 40°C and a 50 / 50 wt% toluene / n-heptane mixture, the comparison results of the pervaporation separation index of the pervaporation membranes in Examples 1-2 and Comparative Examples 4-5 are as follows: Figure 4 As shown.
[0060] The permeation flux of the pervaporation membrane in Comparative Example 4 was 1230 gm. -2 h -1The separation factor was 10.6, resulting in a pervaporation separation index of 11.81 kg m³. -2 h -1 The permeation flux of the pervaporation membrane in Comparative Example 5 was 2050 gm³. -2 h -1 The separation factor was 6.26, resulting in a pervaporation separation index of 10.78 kg m³. -2 h -1 .
[0061] In summary, this invention modifies the polyether-polyamide block copolymer by using aryl diglycidyl ether to crosslink it, so that the separation layer is composed of aryl diglycidyl ether-crosslinked modified polyether-polyamide block copolymer. This allows the pervaporation membrane to improve membrane permeation flux while ensuring membrane separation selectivity, thus exhibiting excellent overall separation performance.
[0062] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A pervaporation membrane, characterized in that, The pervaporation membrane comprises a base membrane and a separation layer stacked together, wherein the separation layer comprises an aryl diglycidyl ether crosslinked modified polyether-polyamide block copolymer.
2. The pervaporation membrane according to claim 1, characterized in that, In the aryl diglycidyl ether crosslinked modified polyether-polyamide block copolymer, the aryl diglycidyl ether includes at least one of bisphenol A diglycidyl ether, bisphenol S diglycidyl ether, and bisphenol F diglycidyl ether.
3. The pervaporation membrane according to claim 1, characterized in that, The base membrane includes a polytetrafluoroethylene filter membrane.
4. The pervaporation membrane according to claim 3, characterized in that, The pore size of the polytetrafluoroethylene filter membrane is 0.1-0.45 μm.
5. The method for preparing the pervaporation membrane according to any one of claims 1-4, characterized in that, Includes the following steps: The polyether-polyamide block copolymer solution was coated onto the surface of the base film, and then crosslinked and modified in an aryl diglycidyl ether solution to obtain the final product.
6. The preparation method according to claim 5, characterized in that, The method for preparing the polyether-polyamide block copolymer solution includes the following steps: The polyether-polyamide block copolymer is prepared by mixing it with a solvent and heating it.
7. The preparation method according to claim 6, characterized in that, The solvent includes N,N-dimethylformamide; And / or, the mass fraction of the polyether-polyamide block copolymer solution is 8-12 wt%; And / or, the heating temperature is 90-110℃, and the heating time is 2-3h.
8. The preparation method according to claim 5, characterized in that, The coating method includes spin coating, and the spin coating speed is 300-1100 rpm; And / or, the coating is then dried, the drying process being carried out at 25-30°C for 12-24 hours, followed by drying at 40-140°C for 3-12 hours.
9. The preparation method according to claim 5, characterized in that, The solvent in the aryl diglycidyl ether solution includes N,N-dimethylformamide; And / or, the mass fraction of the aryl diglycidyl ether solution is 2-10 wt%; And / or, the crosslinking modification temperature is 35-45℃, and the crosslinking modification time is 12-24h; And / or, the crosslinking modification is followed by drying, the drying temperature is 100-120℃, and the drying time is 3-6h.
10. The application of the pervaporation membrane according to any one of claims 1-4 in the separation of alkane / aromatic mixtures.